2015
DOI: 10.1038/ki.2014.241
|View full text |Cite
|
Sign up to set email alerts
|

Polycystin deficiency induces dopamine-reversible alterations in flow-mediated dilatation and vascular nitric oxide release in humans

Abstract: Autosomal dominant polycystic kidney disease (ADPKD) is a renal hereditary disorder associated with increased cardiovascular mortality, due to mutations in polycystin-1 and polycystin-2 genes. Endothelial polycystin-deficient cells have an altered mechanosensitivity to fluid shear stress and subsequent deficit in calcium-induced nitric oxide release, prevented by dopamine receptor stimulation. However, the impact of polycystin deficiency on endothelial function in ADPKD patients is still largely unknown. Here … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
50
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 51 publications
(54 citation statements)
references
References 31 publications
4
50
0
Order By: Relevance
“…Consistent with this finding, Lothioir et al [21] recently reported that FMD induced by warm-ischemia, but not that induced by NO, is impaired in ADPKD. Studying 21 normotensive patients (eGFR 99 ± 18 mL/min/1.73 m 2 , 36% smokers) they found a maintained ability to dilate vessels following infusion of an NO-donor, while warm ischemia led to a markedly blunted response in patients as compared to controls.…”
Section: Discussionsupporting
confidence: 61%
“…Consistent with this finding, Lothioir et al [21] recently reported that FMD induced by warm-ischemia, but not that induced by NO, is impaired in ADPKD. Studying 21 normotensive patients (eGFR 99 ± 18 mL/min/1.73 m 2 , 36% smokers) they found a maintained ability to dilate vessels following infusion of an NO-donor, while warm ischemia led to a markedly blunted response in patients as compared to controls.…”
Section: Discussionsupporting
confidence: 61%
“…Autosomal dominant polycystic kidney disease patients have cardiovascular complications that are thought to be related to the presence of abnormal polycystins in endothelial cells that may interfere with shear stress mechanotransduction; however, there are conflicting findings regarding whether patients with autosomal dominant polycystic kidney disease present conduit artery endothelial dysfunction as assessed by RH-FMD (15,50). Lorthioir et al (56) performed radial artery RH-FMD and hand-warming SS-FMD in patients with autosomal dominant polycystic kidney disease and observed an impaired SS-FMD but similar RH-FMD compared with control subjects with no difference in the shear stress stimuli (SS or RH) between groups. Thus patients with autosomal dominant polycystic kidney disease may have impairments in mechanotransduction of sustained, but not necessarily transient, shear stress.…”
Section: Rh-fmd Versus Ss-fmd In Populations With Increased Cardiovasmentioning
confidence: 99%
“…It was shown that ADPKD patients had significantly less vasodilation during sustained flow increases, as well as a total loss of NO release when compared to those without ADPKD. When ADPKD patients were administered brachial infusions of 0.25-0.5 μg/kg/min of dopamine, there was an increase in flow-mediated dilation, and a statistically significant increase in dilatory response at the highest dose [80]. According to these results, dopamine receptors may facilitate a connection between primary cilia, NO, and blood pressure regulation in ADPKD patients [1].…”
Section: Dopamine Signalingmentioning
confidence: 85%